The transport and fate of microplastic fibres in the Antarctic: The role of multiple global processes - Cunningham, Eoghan M.; Rico Seijo, Nuria; Altieri, Katye E.; Audh, Riesna R.; Burger, Jessica M.; Bornman, Thomas G.; Fawcett, Sarah; Gwinnett, Claire M. B.; Osborne, Amy O.; Woodall, Lucy C. (Frontiers in Marine Science, 2022)
Understanding the transport and accumulation of microplastics is useful to determine the relative risk they pose to global biodiversity. The exact contribution of microplastic sources is hard to elucidate; therefore, investigating the Antarctic Weddell Sea, an area known for its remoteness and little human presence (i.e. limited pollution sources), will help us to better understand microplastic transportation. Here, we investigate the presence of microplastics in a range of Antarctic sample media including air, seawater, and sediment. We hypothesised that multiple transportation processes including atmospheric and oceanic vectors determine the presence of microplastics in the Antarctic. Using techniques including Polarised Light Microscopy and Raman Spectrometry, we identified mostly fibres and categorised them based on their optical and chemical properties. A total of 47 individual microplastic categories (45 of which were fibres) were identified in the air, seawater, and sediment samples. The majority of categories did not overlap multiple media (42/47); however, four fibre categories were present in both air and water samples, and another fibre category was found in all three media (category 27). We suggest that the large variety of fibres identified and the overlap of fibre categories among media indicates that the pollution may result from multiple diffuse sources and transportation pathways. Additionally, our Air Mass Back Trajectory analyses demonstrates that microplastic fibres are being transported by air masses or wind, and strongly suggests that they are transported to the Antarctic from southern South America. We also propose that fibres may be transported into the Antarctic in subsurface waters, and as pollution was identified in our sediment and additional sea ice samples, we suggest that the coastal and Antarctic deep sea may be a sink for microplastic fibres. The results shown here from a remote, near-pristine system, further highlight the need for a global response to the plastic pollution crisis.